Translating tuberculosis control policy into practice: Planning and budgeting challenges at a primary healthcare center - Mujtahidah, Mujtahidah; Rahmilah, Mitha (PT. Mega Science Indonesia, 2025)
Tuberculosis (TB) remains one of the most prevalent communicable diseases in Indonesia, with high morbidity and mortality rates, particularly in urban areas such as Makassar city. This study aimed to examine the planning and budgeting processes of the TB control program at the Tarakan Public Health Center (PHC) in Makassar city. A qualitative descriptive study was conducted via document analysis, direct observations, and in-depth interviews with four key informants (TB program managers, healthcare workers, and community health volunteers involved in TB control). Thematic analysis was used to identify patterns related to program planning, budgeting, implementation, and barriers to program implementation. The TB control program at Tarakan PHC followed national guidelines but faced local challenges, including insufficient early case detection, limited community awareness, and strong social stigma. Budget allocations fluctuate yearly, with IDR 12,800,000 allocated in 2023 and increasing to IDR 25,000,000 in 2024, affecting the program’s sustainability. Patient nonadherence to treatment, often due to perceived recovery, economic hardship, and stigma, was a major barrier. In response, the PHC implemented activities such as active case finding, contact tracing, default tracing, treatment supervision, and preventive therapy, supported by community engagement. Between 2020 and 2024, 226 TB cases were identified. Although national policy supports TB control efforts, local implementation is hindered by behavioral, operational, and financial constraints. Consistent budget allocation, targeted health education, and stronger community involvement are essential for improving treatment outcomes and supporting TB elimination strategies at the primary care level.